Combined transcriptional and metabolomic analysis of flavonoids in the regulation of female flower bud differentiation in Juglans sigillata Dode - Jinyan Chen; Wenwen Li; Wen’ e Zhang; Chunxiang Li; Ruipu Wang; Xuejun Pan; Jian Peng (BMC Plant Biology)
Abstract Juglans sigillata Dode is rich in flavonoids, but the low ratio of female to male flower buds limits the development of the J. sigillata industry. While the abundance of flavonoids in J. sigillata is known, whether flavonoids influence female flower bud differentiation has not been reported. In this study, we explored the regulatory mechanisms of gene expression and metabolite accumulation during female flower bud differentiation through integrated transcriptomic and metabolomic analyses. Our findings revealed that flavonoid biosynthesis is a key pathway influencing female flower bud differentiation, with metabolites primarily shifting towards the isoflavonoid, flavone, and flavonol branches. Structural genes such as chalcone synthase, dihydroflavonol 4-reductase, flavonol synthase, and flavonoid 3',5'-hydroxylase were identified as playing crucial regulatory roles. The expression of these genes promoted the accumulation of flavonoids, which in turn influenced female flower bud differentiation by modulating key regulatory genes including Suppressor of Overexpression of Constans1, Constans, Flowering Locus T, and APETALA1. Furthermore, transcription factors (TFs) highly expressed during the physiological differentiation of female flower buds, particularly M-type MADS, WRKY, and MYB, were positively correlated with flavonoid biosynthesis genes, indicating their significant role in the regulation of flavonoid production. These results offer valuable insights into the mechanisms of female flower bud differentiation in J. sigillata and highlight the regulatory role of flavonoids in plant bud differentiation.